The human right to food as a U.S. nutrition concern, 1976-2006 - Messer, Ellen; Cohen, Marc J. (International Food Policy Research Institute, 2007)
For 30 years, U.S. food and nutrition scientists and policymakers concerned with food and nutrition have explored the possibility of making the human right to food (HRF) the moral and legal cornerstone of U.S. domestic and international initiatives in this area. The U.S. government has consistently opposed formal right-to-food legislation, labeling it as overly burdensome and inconsistent with constitutional law. In contrast, anti-hunger advocates have favored a rights-based framework as a way to hold government accountable for improving the nutritional situation of its poorest citizens and for saving lives and preventing malnutrition in developing countries. The U.S. government has continually expanded food and nutrition assistance at home and abroad, but not within a human rights framework. What might a human rights perspective add, and what are the continuing rationales of the opposition? Using as touchstones U.S. government and nongovernmental organization (NGO) testimonies from the 1976 Right to Food Resolution congressional debate and the 1996 World Food Summit, which featured U.S. opposition to HRF language, the U.S. government and NGO HRF positions are traced from 1976 to 2006. Qualitative analyses of historical policy position papers, testimonies, research reports, and the popular nutrition literature are used to evaluate how human rights and the HRF—as framing and rhetoric—have influenced nutrition policy, public and official understanding, and outreach. In this documentation process, we also integrate information from the wider “human rights” positions of the food-and-nutrition advocacy community, including Food First, Bread for the World, the Food Research and Action Center, the community food security movement, and charitable food assistance agencies, to demonstrate where these different advocacy agents, organizations, and agendas fit in this process of advancing a HRF sensibility.